2019
DOI: 10.1001/jama.2019.17379
|View full text |Cite
|
Sign up to set email alerts
|

Development of Risk Prediction Equations for Incident Chronic Kidney Disease

Abstract: Take-down policy If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
179
4
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 169 publications
(211 citation statements)
references
References 44 publications
6
179
4
4
Order By: Relevance
“…The findings of the current study about the association of parity number with incident CVD among women are consistent with a meta-analysis study on this issue by Li et al [8]. in which they found a non-linear J-shaped dose-response relationship between the number of parity and CVD among women.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The findings of the current study about the association of parity number with incident CVD among women are consistent with a meta-analysis study on this issue by Li et al [8]. in which they found a non-linear J-shaped dose-response relationship between the number of parity and CVD among women.…”
Section: Discussionsupporting
confidence: 92%
“…They also found that each live birth was associated with a 1% non-significant increased risk for CVD mortality (I 2 = 86.4%). It should be noted that the significant heterogeneity in these two meta-analyses [8,20] could be related to different study populations, sample sizes and other epidemiologic aspects of studies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Diabetes is a risk factor for both CKD and CVD (3,4,8). To date, various models have been proposed for the prediction of T2DM (9,10), CKD (11), and CVD (10,(12)(13)(14)(15) separately. Most of the previous models were comprised of non-laboratory measures.…”
Section: Introductionmentioning
confidence: 99%